Analysis of the connection between the Best Linear Unbiased Prediction (BLUP) based breeding values and estimated herd effects in Hungarian pig breeds - Vígh, Zsófia; Nagy, Imre; Farkas, János; Csató, László (Acta Agraria Kaposváriensis, 2005)
The analysis was conducted using station test data of several Hungarian pig breeds that was collected between 1993–1999. Duration of the test, total amount of consumed feed and valuable cuts were taken into account in the analysis. Based on these traits the random distribution of the animals across the herds of origin was tested. The phenotypic measurements of all traits were positively associated with the herds of origin. Animals with favourable measurements originated from herds that provided good environmental circumstances prior to the station test. This environmental effect was substantially reduced by BLUP, as the predicted breeding values were mainly independent from the predicted herd effects. Based on the results it could be concluded that the BLUP based breeding values were much less biased than the phenotypic measurements.
Keywords: phenotype; breeding value; environmental factor; interaction